2014
DOI: 10.1016/j.apcatb.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the low temperature oxidation performance over a Pt and a Pt–Pd diesel oxidation catalyst

Abstract: The influence of hydrogen over platinum and combined platinum-palladium diesel oxidation catalysts were investigated on the oxidation kinetics of CO, HC and NO. Although H 2 has been reported to have a positive effect on CO and HC oxidation as well as NO 2 formation over platinum catalysts, there is still uncertainty whether this is due to the temperature rise caused by H 2 oxidation or the result of a change in the reaction kinetics of CO, HC and NO oxidation by the production of intermediate species. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 24 publications
(26 reference statements)
3
38
0
Order By: Relevance
“…In principle, low performance of hydrocarbons oxidation concerns all engines which produce exhaust gases at low temperatures, e.g. diesel engines under low loads [22].…”
Section: Performance Of the Catalytic Convertermentioning
confidence: 99%
“…In principle, low performance of hydrocarbons oxidation concerns all engines which produce exhaust gases at low temperatures, e.g. diesel engines under low loads [22].…”
Section: Performance Of the Catalytic Convertermentioning
confidence: 99%
“…(1) Surface components balance for each surface species w in each tank k was described by transient equation shown in Equation (2). When steady state condition is achieved, the derivative term in Equation (2) turns to zero.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…For example it is restricted by thermodynamics at high temperature, it possess hysteresis phenomenon during heating and cooling, it is structure sensitive and the reaction is inhibited by HC and CO at low temperature [1]. Recently, it has also been reported that addition of H2 may boost the NO oxidation reaction over Pt catalysts [2,3]. For this reason, kinetic studies of NO oxidation over Pt/Al2O3 have gained a lot of interests from a number of research groups.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches can be described as i) hydrogen addition directly to the SCR, ii) Pt/Al2O3 -DOC placement in the front of the SCR and iii) hydrogen addition upstream the DOC and the SCR [19][20][21]. The well know storage limitations of hydrogen for automotive applications could be solved through the carbon free process of on-board catalytically production of hydrogen through ammonia exhaust gas reforming.…”
Section: No/nh3 -Scr (Standard Scrmentioning
confidence: 99%